Superiority of cardiac magnetic resonance derived left-ventricular ejection fraction in the identification of true acute myocardial infarction among MINOCA patients. (14th October 2021) - Mantzouranis, M; Leontsinis, I; Sakalidis, A; Klettas, D; Avramidis, D; Patsourakos, N; Stougiannos, P; Dimitriadis, K; Thomopoulos, C; Poulimenos, L; Mamarellis, I; Milkas, A; et al.
Abstract: Background/Introduction: MINOCA constitutes a clinical entity characterized by heterogeneous and poorly understood pathophysiological substrate, whereas current knowledge leaves significant gaps regarding the identification, risk stratification and therapeutical approach of these patients. Purpose: The aim of our study is to investigate the potential role of clinical, hemodynamic, laboratory and imaging parameters in the early identification of true acute myocardial infarction (AMI) among patients with a working diagnosis of MINOCA. Methods: Our study population included 62 patients admitted with acute coronary syndrome (ACS) fulfilling the diagnostic criteria of MINOCA. A subsequent cardiac magnetic resonance (CMR) performed at 54 patients demonstrated an ischemic pattern of late gadolinium enhancement (LGE) confirming the diagnosis of true AMI in 15 cases (27.8%). Other findings included Takotsubo syndrome (n=19; 35.2%) and myocarditis (n=4; 7.4%), whereas CMR failed to reveal abnormal findings at 16 cases (29.8%). Results: Focusing on the combined population of true AMI and clear CMR groups (n=31; 51.6% male; mean age: 58±12 years old; 42% hypertensives (HTN), 16% with history of diabetes mellitus (DM), 28.6% smokers) no significant difference was observed regarding classic cardiovascular risk factors (HTN, DM, smoking, age, dyslipidemia) except for a tendency of overrepresentation of female sex (r=0.354; p=0.051) in the true AMI group. Coronary angiographic (CA) findings did not differ between the two groups: clear vessels: 16/31 (51.6%); lesions causing ≤50% stenosis: 7/31 (22.6%); bridges: 4/31 (12.9%); spontaneous coronary artery dissection (SCAD): 2/31 (6.5%); slow flow phenomenon or spontaneous epicardial spasm: 2/31 (6.5%). No difference was observed in treatment approach with beta-blockers, renin-angiotensin system blockers, statins or the selection of no, single or dual antiplatelet strategy. Univariate regression analysis demonstrated that CMR derived left-ventricular ejection fraction (CMR-LVEF) (OR, 0.846; CI 95%: 0.742–0.965; p=0.012), as well as admission ECG abnormalities (OR, 0.154; CI 95%: 0.026–0.914; p=0.04), admission (OR, 5.689; CI 95%: 1.374–23.553; p=0.016) and peak troponin levels (OR, 15.874; CI 95%: 2.486–101.367; p=0.003) were the only parameters significantly related to a true AMI. Statistical significance was retained in multivariate models adjusted for age, gender, history of HTN and DM. On the contrary echocardiography derived LVEF failed to predict true AMI. Conclusions: These preliminary results further highlight the need of an early CMR evaluation of MINOCA patients. A timely identification of true AMI is expected to improve patient outcomes by guiding the treatment approach. Funding Acknowledgement: Type of funding sources: None.